2017
DOI: 10.1177/2167702617733817
|View full text |Cite
|
Sign up to set email alerts
|

Negative Urgency Mediates the Relation Between Genetically Influenced Serotonin Functioning and Alcohol Problems

Abstract: Serotonin (5-HT) functioning is associated with alcohol problems. However, the mechanisms underlying this association remain unclear. The current study tested whether five separate dimensions of impulsivity (UPPS-P) mediated the relation between a polygenic score indexing 5-HT functioning and alcohol problems and whether any of these paths were moderated by age. Results showed that a 5-HT polygenic score predicted alcohol problems indirectly through negative urgency, but not any other facet of impulsivity. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 69 publications
(111 reference statements)
0
11
0
Order By: Relevance
“…Neurochemically, negative urgency may reflect deficient 5-hydroxytryptamine (5-HT) and lower dopamine activity in the OFC and vmPFC (Floresco and Tse, 2007; Cyders and Smith, 2008), leading to less inhibition of both basal ganglia- and extended amygdala-subserved impulses. Accordingly, a composite polygenic 5-HT score predicted alcohol problems via an increase in negative urgency and not via other measures of impulsivity (Carver et al, 2011; Wang and Chassin, 2018). Evidence of lower 5-HT activity and responsiveness is likewise seen in bulimia nervosa with regard to the presence and severity of binge symptoms (Cyders and Smith, 2008).…”
Section: Neurocircuitry Implicated In Negative Urgency and Addictionmentioning
confidence: 99%
“…Neurochemically, negative urgency may reflect deficient 5-hydroxytryptamine (5-HT) and lower dopamine activity in the OFC and vmPFC (Floresco and Tse, 2007; Cyders and Smith, 2008), leading to less inhibition of both basal ganglia- and extended amygdala-subserved impulses. Accordingly, a composite polygenic 5-HT score predicted alcohol problems via an increase in negative urgency and not via other measures of impulsivity (Carver et al, 2011; Wang and Chassin, 2018). Evidence of lower 5-HT activity and responsiveness is likewise seen in bulimia nervosa with regard to the presence and severity of binge symptoms (Cyders and Smith, 2008).…”
Section: Neurocircuitry Implicated In Negative Urgency and Addictionmentioning
confidence: 99%
“…55 and 5-HT has been implicated in fly ethanol sedation. 59 Furthermore, there is a large literature linking 5-HT to alcohol problems in humans (eg, [60][61][62][63][64] ). These findings collectively suggested that there could be mechanistic connections between serotonergic neurons and the effect of dietary yeast on ethanol sedation.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary yeast influences brain 5-HT content in flies 55 ; 5-HT likely plays a role in fly ethanol sedation, 59 and 5-HT is connected to problematic alcohol consumption in humans (eg, [60][61][62][63][64] ). Additionally, serotonergic neurons and serotonin signaling are important for hunger/satiety and feeding behavior in both larval and adult flies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous lines of evidence indicating that decreased levels of 5HT are strongly associated with increased alcohol consumption and risk for future alcohol problems (145147). One recent study reported that negative urgency (as measured by UPPS-P) mediated the relationship between alcohol abuse and genetically driven decreases in 5HT availability (148). In this study, higher polygenic 5HT scores (indicating lower 5HT function) were positively correlated with higher self-reported negative urgency and greater levels of alcohol consumption.…”
Section: Neural and Genetic Correlates Of Negative Urgency And Potentmentioning
confidence: 99%